Stability Analysis For Tumour Growth Model Through The Lambertz W Function - Priya, Krishna (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we investigate the stability of the tumor growth system. An approach of the matrix Lambertz W function for the analytical solution to system of delay differential equations is applied to this problem and compared with the result obtained by a bifurcation analysis.